Сутнісна характеристика інтернаціоналізації економіки України - Ільчук, П. Г. (Видавництво Львівської політехніки, 2014)
Визначено сутність категорії «інтернаціоналізація» у працях зарубіжних та українських вчених, запропоновано авторське трактування поняття «інтернаціоналізація» як «розширення та/або перенесення діяльності підприємства за межі ринку країни базування (національного) на закордонні ринки з врахуванням і адаптацією діяльності до умов господарювання на цих ринках». Проаналізовано сучасний стан та напрями співпраці України з іншими державами. Зокрема, розглянуто географічну структуру та динаміку зовнішньої торгівлі України товарами та послугами, кількість та географічне розташування представництв українських підприємств за кордоном, обсяги прямих інвестицій з України в економіку зарубіжних країн. Виявлено, що економіка України готова до ведення підприємницької діяльності на закордонних ринках, яка може мати такі прояви: експорт продукції; створення представництва (філії, відділення) на території іноземної держави; прямі інвестиції (акціонерний капітал) як джерело фінансування підприємств на цих ринках. In the current global economic system businesses normally operate in many geographic markets and therefore the study of the key problems of business internationalization, such as an enterprise entering a foreign market or foreign market presence activities is very relevant at the moment. In this article, we systematize different approaches used by international and local researchers to reveal the essence of “internationalization” category as well as their own definition of “internationalization”. We also examine actual status and the dynamics of internationalization of the Ukrainian economy. In our article, we analyze the current state and possible vectors of cooperation between Ukraine and other countries. In particular, we review the geographical structure and the dynamics of Ukraine’s foreign trade in goods and services, the number and geographical locations of the representative offices of Ukrainian companies abroad, the amounts of Ukrainian direct investments in the foreign economies. It appears, that Ukrainian economy is ready for entrepreneurial activity in foreign markets. First of all, it means an export of the goods produced in Ukraine, setting up the representative offices overseas, direct investments (share capital) as the enterprise finance source in the markets abroad. The investigation of the geographical structure of Ukraine’s foreign trade in goods and services reveals, that Ukrainian companies focused their activities (apart of the local market) on the three main geographical markets – European, Asian and CIS (Commonwealth of Independent States). First of all, this is explained by the geographical proximity of this markets to Ukraine. As for the Ukraine’s services export, the main importers are CIS and European countries followed by Asian and American regions. Hence, the enterprises working with services delivering expand to the foreign markets more actively. The systematization of the information concerning representative offices of Ukrainian companies abroad has shown their presence in five geographical regions: 1 in Africa, 4 in America, 13 in Asia, 15 in Europe and 134 in CIS countries. The geographical location of the highest fraction of the representative offices abroad coincides with the geographical regions where Ukraine exports most of the goods and services. This is explained by the mental and cultural connection of Ukraine with CIS countries, where Ukraine exports as much as 34,85% of goods and 41,25% of services. Based on the consolidated data concerning Ukrainian direct investments abroad, it was found out that 88,49 % of Ukrainian direct investments were placed in Cyprus. This fact confirms, first of all, the efforts to disguise the real profits of Ukrainian enterprises via collaboration with Cyprus offshore companies. One of the results of the undertaken research is the definition of the essence of “internationalization” category used by international and local researchers in their studies. Taking into consideration different approaches of international researchers and the necessity to adopt to the business conditions of foreign markets we propose author definition of the “internationalization” concept as the “expansion and/or the transfer of the entrepreneurial activities outside the national home market to the foreign markets taking into account and adopting activities to the business conditions in these markets”.
Essential characteristics of the Ukrainian economy internationalization
Keywords: інтернаціоналізація; глобалізація; зовнішня торгівля; іноземні інвестиції; internationalization; globalization; international trade; foreign investments